Notes on common macrobenthic reef invertebrates of Tubbataha Reefs Natural Park, Philippines - Dolorosa, Roger G. (Science Diliman, 2012)
Macrobenthic reef invertebrates are important reef health indicators and fishery resources but are not very well documented in Tubbataha Reefs Natural Park. To provide notes on the species composition and the abundance and size of commonly encountered macrobenthic reef invertebrates, belt transects survey in intertidal, shallow, and deep subtidal reef habitats were conducted. In total, 18 species were recorded, six of which were echinoderms and 12 were mollusks, which include the rare giant clam Hippopus porcellanus. Only the giant clam Tridacna crocea and the top shell Trochus niloticus occurred in all seven permanent monitoring sites but the two species varied in densities across depths. There was also an outbreak of crown-of-thorns (COTs) sea stars in some sites. The large variation in the density of each species across sites and depths suggests niche differences, overharvesting, or their recovery from having been overly exploited. Separate monitoring areas for each commercially important species are suggested to determine how their populations respond to poaching and their implications on the park's long term management. [ABSTRACT FROM AUTHOR]